Sleep Complaints and the 24‐h Melatonin Level in Individuals with Smith–Magenis Syndrome: Assessment for Effective Intervention. (14th October 2016) - Spruyt, Karen; Braam, Wiebe; Smits, Marcel; Curfs, Leopold MG
Summary: Aims: Individuals with Smith–Magenis syndrome (SMS) are reported to have a disrupted circadian rhythm. Our aim was to examine problematic sleeping in those attending our sleep clinic for the first time. Methods: At intake, caregivers of 50 children and nine adults with SMS were surveyed about the sleep pattern and potential melatonin administration. Sampling of salivary melatonin levels was performed. Results: At intake, exogenous melatonin was used by 16 children (27.1% of sample; 56.3% male) with mean age 6.8 ± 2.8 years, whereas 34 children (57.6%; 7.5 ± 4.8 years old; 64.7% male) and nine adults (15.3%; 36.8 ± 15.3 years old; 44.4% male) were not taking melatonin at intake. Participants were reported to have problems with night waking and early awakenings regardless of melatonin administration. Overall, moderate to high levels of salivary melatonin at noon were found in individuals with SMS. In particular, children with SMS showed a disrupted melatonin pattern. Furthermore, the endogenous melatonin level, age, and gender may potentially interact, yielding the severity range of sleep disturbances reported in SMS. Conclusion: Treatment of sleep problems in SMS is complex, and our findings may support person‐centered sleep and medication management. Future clinical trials including larger groups may shed light on such approaches.